Regulation of Mitogen-Activated Protein Kinases in Cardiac Myocytes through the Small G Protein Rac1 - Clerk, Angela (American Society for Microbiology, 2001)
Small guanine nucleotide-binding proteins of the Ras and Rho (Rac, Cdc42, and Rho) families have been implicated in cardiac myocyte hypertrophy, and this may involve the extracellular signal-related kinase (ERK), c-Jun N-terminal kinase (JNK), and/or p38 mitogen-activated protein kinase (MAPK) cascades. In other systems, Rac and Cdc42 have been particularly implicated in the activation of JNKs and p38-MAPKs. We examined the activation of Rho family small G proteins and the regulation of MAPKs through Rac1 in cardiac myocytes. Endothelin 1 and phenylephrine (both hypertrophic agonists) induced rapid activation of endogenous Rac1, and endothelin 1 also promoted significant activation of RhoA. Toxin B (which inactivates Rho family proteins) attenuated the activation of JNKs by hyperosmotic shock or endothelin 1 but had no effect on p38-MAPK activation. Toxin B also inhibited the activation of the ERK cascade by these stimuli. In transfection experiments, dominant-negative N17Rac1 inhibited activation of ERK by endothelin 1, whereas activated V12Rac1 cooperated with c-Raf to activate ERK. Rac1 may stimulate the ERK cascade either by promoting the phosphorylation of c-Raf or by increasing MEK1 and/or -2 association with c-Raf to facilitate MEK1 and/or -2 activation. In cardiac myocytes, toxin B attenuated c-Raf(Ser-338) phosphorylation (50 to 70% inhibition), but this had no effect on c-Raf activity. However, toxin B decreased both the association of MEK1 and/or -2 with c-Raf and c-Raf-associated ERK-activating activity. V12Rac1 cooperated with c-Raf to increase expression of atrial natriuretic factor (ANF), whereas N17Rac1 inhibited endothelin 1-stimulated ANF expression, indicating that the synergy between Rac1 and c-Raf is potentially physiologically important. We conclude that activation of Rac1 by hypertrophic stimuli contributes to the hypertrophic response by modulating the ERK and/or possibly the JNK (but not the p38-MAPK) cascades.